2013
DOI: 10.11648/j.ijefm.20130102.16
|View full text |Cite
|
Sign up to set email alerts
|

Systematic Approach for Improving Medical Service Quality, International Journal of Economics

Abstract: Abstract:The purpose of this research is to discuss the characteristics of medical services quality in the hospital institutions. This study discusses the characteristics of medical services quality in the hospital institutions, combining the analysis of services quality deficiency and investigation then figuring out the method of improvements to focus on service deficiency. This research applied three kinds of technologies: The service quality questionnaire surveys, the gap model analysis and the quality func… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 7 publications
0
2
0
Order By: Relevance
“…According to these conditions, customers reduce medical service scores and trust is lost. Yang and Huang (2013) confirm that diagnosis and discussing symptoms are key service quality items for doctors. Shieh et al, (2010) indicate that the critical success factor for medical service quality is that doctors explain treatment and results in detail.…”
Section: Discussionmentioning
confidence: 58%
See 1 more Smart Citation
“…According to these conditions, customers reduce medical service scores and trust is lost. Yang and Huang (2013) confirm that diagnosis and discussing symptoms are key service quality items for doctors. Shieh et al, (2010) indicate that the critical success factor for medical service quality is that doctors explain treatment and results in detail.…”
Section: Discussionmentioning
confidence: 58%
“…Quintela et al, (2011) showed that individual concerns and immediate services provided to customers are important service qualities. Yang and Huang (2013) indicated that symptom diagnosis and professional explanation and discussion with doctors are important service quality items. Shieh et al, (2010) indicated that detailed medication processes and results from doctors are critical success factors for medical service quality.…”
Section: Medical Tourismmentioning
confidence: 99%